"STAUROPHOBIA" : FEAR OF THE CROSS BASED ON HATE SPEECH AND SOME WAYS TO FACE IT - Borgias, Fransiskus; Stanislaus, Surip (LOGOS, 2024)
This article explores the phenomenon of staurophobia, “fear of the cross”. There are negative discourses toward Christians and Christ’s cross, called staurophobia. It is related to an attitude towards Christ, either accepting Christ on the one hand, or rejecting Christ, on the other. Since the beginning of Christian history in New Testament, the cross (stauros) has been a sign of contradiction. It becomes a stumbling block to non-Christians, while for Christians, it is a sign of salvation. What is Christian’s attitude, if, on the basis of staurophobia, non-Christians develop hate speech against them? New Testament gives us glimpses of answers that people should not cause violence. Based on the historical comparative study of some New Testament theological discourses, I propose that Christians should develop a calm socio politico theological attitude toward the negative discourses aroused by outsiders. I also endorse Christians to develop a sense of humour to confront such negative discourses on the cross and crucifix, as once practiced by Francis of Assisi in his encounter with Sultan Malik al-Kamil in Damieta, Egypt